Beyond Good Governance: An Ultimate Key Success for Higher Education Quality - Somariah Fitriani; Hery Muljono (STKIP Singkawang, 2019)
The purpose of the study was to find out the effect of leadership and cultural academic on good governance, which focused on transparency and accountability aspects. The study adopted a quantitative approach by using causal survey method with path analysis technique, which was to test the hypothesis. Thirty-one respondents consisting of lecturers and staff of graduate school of Universitas Muhammadiyah Prof. DR. HAMKA (UHAMKA) were taken as a sample by using Taro Yamane formula. Questionnaire of three variables was distributed to the respondents by employing a Likert scale. For data analysis, the study used SPSS 21 to test data normality, linearity, coefficient correlation, and path coefficient. The research has revealed that: 1) leadership has a direct positive effect on academic culture; 2) leadership has a direct positive impact on good governance; 3) academic culture has a direct positive effect on good governance; and 4) the implementation of good governance is in accordance with its principles, i.e., transparency and accountability which has excellent impact to human resource quality, particularly in term of the increasing number of research and community service. It can be concluded that organization coherence is well created on account of the implementation of good governance principles, which is supported by strong leadership and academic culture. On the other word, strong leadership plays a vital role in effective governance.